Optimal sequential contests - Toomas Hinnosaar (Theoretical Economics, 2024)
I study sequential contests where the efforts of earlier players may be disclosed to later players by nature or by design. The model has many applications, including rent seeking, R&D, oligopoly, public goods provision, and tragedy of the commons. I show that information about other players' efforts increases the total effort. Thus, the total effort is maximized with full transparency and minimized with no transparency. I also show that in addition to the first-mover advantage, there is an earlier-mover advantage. Finally, I derive the limits for large contests and discuss the limit to perfectly competitive outcomes under different disclosure rules.
Keywords: C72; C73; D72; D82; D74; 330; Contest design; oligopoly; public goods; R&D; rent-seeking